Feasibility study of Maisotsenko indirect evaporative air cooling cycle in Iran - Rezaee, Vahid; Houshmand, Arash (GeoScience Engineering, 2015)
This paper presents energy and exergy analysis of air cooling cycle based on novel Maisotsenko indirect evaporative cooling cycle. Maisotsenko cycle (M-cycle) provides desired cooling condition above the dew point and below the wet bulb temperature. In this study, based on average annual temperature, The Iran area is segmented to eleven climates. In energy analysis, wet-bulb and dew point effectiveness, cooling capacity rate and in other hand in exergy analysis, exergy input rate, exergy destruction rate, exergy loss, exergy efficiency, exergetic COP and entropy generation rate for Iran’s whether condition in indicated climates are calculated. By the way, a feasibility study based on water evaporation rate and Maisotsenko cycle had been presented. Energy and exergy analysis results show that the fifth, sixth, seventh and eighth climates are quite compatible and Rasht, Sari, Ramsar and Ardabile cities are irreconcilable with Maisotsenko cycle.